The enhanced cognitive Interview: towards a better use and understanding of this procedure - Paulo, Rui M. (2013)
The Enhanced Cognitive Interview is accepted as one of the most successful techniques for enhancing witness recollection. This type of interview has been studied all over the world (eg, Europe or the USA) and is used by police officers in many different countries (eg, the UK and New Zealand). Nonetheless, it is essential for police officers to understand how, and when, to properly apply this interview. Therefore, we examined the underlying psychological processes involved in this interview, and what research can tells us about the situations and purposes that can benefit from applying it.